E-latter: A smart solution for enhancing administrative services in Tinggarjaya Village - Aslindar, Dwi Astarani; Nasori, Ahmad; Sambodo, Herman; Triyono, Bambang (Universitas Ahmad Dahlan, 2024)
Tinggarjaya Village, located in Jatilawang District, Banyumas Regency, faces several administrative problems. One of them is that official letters are still made manually, which results in poorly organized data storage and limited archive space. This community service aims to overcome these problems through training and assistance related to digital administration, email utilization, and village website development. This program has been implemented and has provided significant benefits, especially in improving administrative efficiency and the capabilities of Tinggarjaya Village human resources.